IDENTIFYING BUSINESS STRATEGY USING SWOT AND PESTEL ANALYSES - Maharani, Nabilla Pramesti; Khalid , Zulvia (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
As a business company, Lite n’ Easy, Australia, This healthy food business company needs to develop in a business environment that is always changing at all times and always has challenges in the market. Therefore, identifying opportunities for company growth needs to be done. This study aims to identify growth opportunities through the integration of SWOT, PESTEL, and Product Life Cycle analysis. SWOT analysis is used to examine the business environment from both internal and external parties of the company consisting of Strengths, Weaknesses, Opportunities, and Threats. While PESTEL analysis is used to examine the external business environment which includes Political, Economic, Social, Technological, and Legal aspects. And for the Product Life Cycle includes the product life process in business. By combining the analysis in this study offers a solution to increase sales of this company's products. This study shows that the benefits of SWOT, PESTEL and Product Life Cycle analysis not only enrich the strategic planning process but also provide a detailed perspective to take advantage of emerging opportunities.